A new quill mite Syringophiloidus pseudonigritae sp. nov. (Prostigmata, Syringophilidae) parasitizing Pseudonigrita arnaudi (Passeriformes, Ploceidae)—a combined description using morphology and DNA barcode data - Glowska, Eliza; Dragun-Damian, Anna; Dabert, Jacek (Zootaxa, 2012)
A new quill mite species Syringophiloidus pseudonigritae sp. nov. is described using a combination of morphological dataand COI sequence data. The mite was found parasitizing a Grey-headed Social-Weaver Pseudonigrita arnaudi (Bonaparte) (Passeriformes, Ploceidae), which was captured in Tanzania and died in a German aviary.